Measuring the influence of energy prices in the price formation mechanism. (June 2018) - Llop, Maria
Abstract: Environmental economics has proposed taxation on energy as a way of mitigating the pollution caused by the production and use of energy based on fossil fuels. However, it is generally assumed that energy is an important component of production costs and that taxes on energy have a detrimental impact on the economy. This paper provides a method of analysing the extent to which energy prices influence the price formation mechanism. The model used is based on a social accounting matrix (SAM). The SAM price model identifies the role of energy prices in the cost and price definition processes. The empirical application is for the Catalan economy and shows that energy prices have a considerable influence on both production and final prices and that different forms of energy exert asymmetric impacts on costs for sectors and consumers. Highlights: A multisectoral model of prices is proposed. The model is defined to isolate the price effects of energy activities. The method disentangles three multiplier effects within total price impacts. The different energy goods impact the sectors of production in a different way.